Supersubstorms (SML < −2500 nT): Magnetic storm and solar cycle dependences. Issue 8 (26th August 2016) - Hajra, Rajkumar; Tsurutani, Bruce T.; Echer, Ezequiel; Gonzalez, Walter D.; Gjerloev, Jesper W.
Abstract: We study extremely intense substorms with SuperMAG AL (SML) peak intensities < −2500 nT ("supersubstorms"/SSSs) for the period from 1981 to 2012. The SSS events were often found to be isolated SML peaks and not statistical fluctuations of the indices. The SSSs occur during all phases of the solar cycle with the highest occurrence (3.8 year −1 ) in the descending phase. The SSSs exhibited an annual variation with equinoctial maximum altering between spring in solar cycle 22 and fall in solar cycle 23. The occurrence rate and strength of the SSSs did not show any strong relationship with the intensity of the associated geomagnetic storms. All SSS events were associated with strong southward interplanetary magnetic field Bs component. The Bs fields were part of interplanetary magnetic clouds in 46% and of interplanetary sheath fields in 54% of the cases. About 77% of the SSSs were associated with small regions of very high density solar wind plasma parcels or pressure pulses impinging upon the magnetosphere. Comments on how SSS events may cause power outages at Earth are discussed at the end of the paper. Key Points: Extremely intense substorms/supersubstorms are often isolated events and are not obvious statistical fluctuations of the geomagnetic indices Supersubstorm occurrence and intensity have no obvious relationship with geomagnetic storm intensity Supersubstorms exhibit annual variation with peak occurrence during spring in SC 22 and fall in SC 23